Efektivitas Media Pembelajaran Interaktif Berbasis Augmented Reality Terhadap Motivasi Belajar Siswa pada Mata Pelajaran IPAS Kelas IV SD Negeri 3 Purwawinangun - Auliah, Fitri; Suryaman, Oman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effectiveness of interactive learning media based on Augmented Reality (AR) in increasing students' learning motivation in Natural and Social Sciences (IPAS) subjects for grade IV of SD Negeri 3 Purwawinangun. The research method used is a quantitative experiment with a one-group pretest-posttest design. The population was 34 grade IV students. The sampling technique used total sampling. The research sample was all 34 grade IV students. The research instruments used in this study were interviews, observations, documentation, and questionnaires. The data analysis techniques used in this study were normality tests, hypothesis tests, and n-gain tests. The results showed that there was an increase in students' learning motivation after using Augmented Reality (AR) media, as indicated by an increase in motivation scores from pretest to posttest, and an N-Gain value of 0.690 which is included in the fairly effective category. Therefore, it can be concluded that interactive learning media based on augmented reality is quite effective in increasing students' learning motivation in IPAS learning for grade IV of SD Negeri 3 Purwawinangun.